Penerapan Etika Bisnis di Industri Perbankan Syariah: Tantangan dan Peluang - Setiawan, Jaka; Faturrahman, Rieno; Sarpini, Sarpini (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
The application of business ethics in the sharia banking industry plays an important role in differentiating sharia banks from conventional banks, with a focus on the values of justice, honesty and transparency. This article analyzes the challenges and opportunities for implementing business ethics in the context of Islamic banking. Some of the main challenges include a lack of understanding of sharia principles, conflicts between profitability and ethical values, as well as regulatory obstacles and competition with conventional banking. However, big opportunities also arise through increasing public trust in sharia financial services, using technology to increase transparency and efficiency, and supporting pro-sharia government regulations. By overcoming these challenges and exploiting existing opportunities, Islamic banking can strengthen its position as a more ethical and sustainable alternative in the global financial industry